Psoriatic onychodystrophy: indices for assessing the severity of psoriatic onychodystrophy (part 2) - A. V. Platonova; A. S. Zhukov; V. R. Khairutdinov; A. V. Samtsov (State Scientific Center of Dermatovenereology and Cosmetology, 2019)
Psoriatic onychodystrophy constitutes an important clinical manifestation of psoriasis and is characterised by multiple symptoms of damage to the nail bed and nail matrix. In order to determine the severity of psoriatic onychodystrophy, as well as the therapeutic efficacy of medications, a unified scale is needed. The article describes the most common indices: NAPSI, mNAPSI, target NAPSI, NAS, PNSS, Baran scale, N-NAIL. In this work, the authors present a methodology for working with each of them, as well as a comparative analysis of detectable symptoms. The conducted literature review indicates the absence of a universal index for assessing the severity of psoriatic onychodystrophy and determines the need to search for new diagnostic algorithms.